Shoulder Injuries in Sport: A Systematic Review - fatahi, Ali; Molavian, Rozhin (Journal of Clinical Physiotherapy Research, 2021)
ABSTRACT Background: The purpose of this study was to, present and discuss the accumulated knowledge involvement in various shoulder injuries and highlight the clinical implications for the evaluation and treatment of shoulder injuries. Shoulder injuries are common in both athletes and non-athletes. Risk factors for shoulder injuries are unknown despite the increase in injury rates. We seek to summarize the causes of shoulder injuries in athletes. Study Design: Systematic review. Methods: Searches were performed on 4 databases using keywords related to shoulder injury factors and a review of all applicable manuscripts was performed. Result: Ninety-three articles met criteria for inclusion. Of the all independent variables that were analyzed, age, overhead throw sport and other sport, professional or amateur, contact and non-contact sports, male and female and related fall in sports were found to be independent risk factors for shoulder injuries. Conclusion: The comparison of sport to non-sport shoulder injury incidence rates suggests that the increased risk of shoulder injuries in young males is mainly attributable to sports injuries. Men are more exposed to upper limb injuries.